IMPORTANCE OF TECHNOLOGIES IN EDUCATION - Rustamova, Adash Eshankulovna; Baxtiyorova, Muslimabonu Shuxrat qizi (INTERNATIONAL CONFERENCES, 2023)
By reading of this article, you are given information about essential role of modern technologies during lessons and some challenges that teachers and students face when they work with them.